2022
DOI: 10.1556/0088.2022.00122
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of toxic elements and chlorophyll fluorescence in the leaves of energy willow (Salix sp.), treated with wastewater solids and wood ash

Abstract: Open-field small plot long-term experiment was set up during 2011 with willow (Salix triandra × S. viminalis ‘Inger’), grown as a short rotation coppice energy crop in Nyíregyháza, Hungary. The sandy loam Cambisol with neutral pH was treated three times (2011, 2013, and 2016) with 15 t ha–1 municipal sewage sludge compost (MSSC) and with 600 kg ha–1 (2011, 2013) or 300 kg ha–1 (2016) wood ash (WA). In 2018 the MSSC-treated plots were amended with 7.5 t ha–1 municipal sewage sediment (MSS), and 300 kg ha–1 WA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…To make phytoextraction effective and the whole process economical, selected plant species must represent specific characteristics including rapid growth (biomass production) and a high degree of metal tolerance (Arthur et al 2005;Shikha and Singh 2021). For these reasons, the best candidates can be found among woody species (Mohsin et al 2019;Simon et al 2022). In addition to the abovementioned characteristics, the efficiency of remediation can be facilitated by genetic modification (e.g., overexpression of genes accountable for metal tolerance and uptake) or by increasing the bioavailability of metals in the growing media (Liu et al 2020;Sarma et al 2021;Trippe and Pilon-Smits 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To make phytoextraction effective and the whole process economical, selected plant species must represent specific characteristics including rapid growth (biomass production) and a high degree of metal tolerance (Arthur et al 2005;Shikha and Singh 2021). For these reasons, the best candidates can be found among woody species (Mohsin et al 2019;Simon et al 2022). In addition to the abovementioned characteristics, the efficiency of remediation can be facilitated by genetic modification (e.g., overexpression of genes accountable for metal tolerance and uptake) or by increasing the bioavailability of metals in the growing media (Liu et al 2020;Sarma et al 2021;Trippe and Pilon-Smits 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Formerly, a sewage settling pond system was operated here as a secondary biological purification unit [ 85 , 86 ]. The sewage settling ponds were recultivated in 2013, and municipal sewage sediment (abbreviated as MSS) located at a 70–110 cm depth was covered with a soil layer [ 87 , 88 ]. Our former sampling and chemical analysis of the MSS [ 87 ] revealed that this wastewater solid is contaminated with potentially toxic elements (abbreviated as PTEs), since the measured values were: As–31.0, Ba–596, Cd–1.23, Cr–1142, Cu–198, Mn–520, Ni–62.8, Pb–278, and Zn–978 mg kg −1 on a dry-matter basis.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the soluble (“plant-available”) element content of the soil, the MSZ 20135 [ 93 ] was followed. The sample preparation procedure and the extraction of 0.5 g soil (<0.1 mm) with Lakanen–Erviö (LE) solution (0.02 M H 4 -EDTA in 0.5 M ammonium acetate buffer and 0.5 M acetic acid, pH 4.65; Lakanen and Erviö, 1971) is described in published articles [ 87 , 88 ].…”
Section: Methodsmentioning
confidence: 99%
“…Due to their influence, certain parameters of the soil change: the pH value of the soil decreases, the total N-, P-, Na-, K-and Ca content increases, the Pb-, Cr-, Cd-, Cu-, Zn-and Ni concentration in the soil also increases. The main problem is that the metals they contain are generally non-degradable pollutants and can accumulate in the food chain in the process of biomagnification (Simon et al 2022, Asati et al 2016, Singh & Agrawal 2007. Some plants have a natural ability to uptake inorganic chemicals (including metals) from soil and sediment, and accumulate them in their tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoremediation is the use of plants and their associated microbes for environmental cleanup. For example, the willow species growing in polluted areas can accumulate significantly higher concentrations of Cd, Pb, and Zn in all their organs than species found in unpolluted areas (Simon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%